Pasture restoration by control of Genista scorpius (L.) DC - Delgado I.; Ochoa M.J.; Sin E.; Barragan C.; Rodríguez J.; Nuez T.; Posadas J.M. (Réhabilitation des pâturages et des parcours en milieux méditerranéens, 2004)
Genista scorpius (L.) DC. is an invading shrub of formerly farmed plots that are now used for grazing. This study examines the effect of removing G. scorpius on forage production with and without mineral fertilization in the semi-arid regions of north-west Spain, as well as the evolution of G. scorpius populations over a 4-year period. The results obtained show that forage production increased from 19.9 kg to 2488.9 kg DM per ha per year, depending on the location and annual rainfall. Fertilization had a significant effect after the third year.
11. Réunion du Sous-Réseau Ressources Fourragères Méditerranéennes du Réseau Coopératif Interrégional FAO-CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 2002/10/29-2002/11/01, Djerba (Tunisia)